INTERPRETATION OF AMBIGUOUS PROVISIONS OF INTERNATIONAL INVESTMENT TREATIES AUTHENTICATED IN TWO OR MORE LANGUAGES - BALCERZAK, Filip (Comparative Legilinguistics, 2014)
The presented article identifies and offers solutions to problems related to interpretation of international investment treaties, which have been authenticated in two or more languages. It focuses on situations when the provisions of investment treaties cause interpretational doubts because their wording is not identical in the official languages of the particular treaty. The scope of the analysis is narrowed down to the provisions concerning the jurisdiction of tribunals, which is justified due to practical implications of jurisdictional considerations in the course of arbitral proceedings. The first part of the article explains relevant applicable general principles of treaty interpretation as expressed in the 1969 Vienna Convention on the Law of Treaties. The second part is a case study, which analyses the problems faced by tribunals in the Kilic Insaat v. Turkmenistan, Berschader v. Russia and Daimler v. Argentina cases. The conclusions presented in the article may serve as a tool in the practice of investor – state arbitration, when implementation of specific provisions of international investment treaties occurs in the course of arbitral proceedings.